Main provisions of the concept of physical therapy for patients with rheumatoid arthritis - Grygus, Igor; Nogas, Anzhela (Journal of Education, Health and Sport, 2020)
The purpose, main tasks and principles of the author's concept are defined, conceptual approaches to the problems of physical therapy of patients with rheumatoid arthritis are analyzed. The main approaches to the prerequisites for the development of the author's concept of restoring the quality of life of patients with rheumatoid arthritis are considered, which include: biological, social and personal prerequisites. A system of restoration and improvement of the quality of life of patients with rheumatoid arthritis has been developed, which consists in the integrated application of rehabilitation measures, taking into account the individual and interdisciplinary approach to each patient in each of the recovery periods. The methodological approaches in accordance with the domains of the International classification of functioning, taking into account the factors that affect the level of functional impairment and quality of life of the patient, are taken into account. It is emphasised that the proposed concept was holistic in nature, based on the targeted use of a comprehensive psychological, pedagogical, medical and rehabilitation approach, physical therapy programmes were individually selected for each patient, taking into account functional joint disability, rheumatoid arthritis activity, quality of life and health status of patients. The article presents the technology of rehabilitation measures to improve the effectiveness of rehabilitation treatment of patients with rheumatoid arthritis, achieve clinical remission, reduce pain, improve joint motor function, prevent deformities and contractures, maintain performance and improve quality of life. It was noted that the realization of the restorative effect in accordance with the tasks of physical therapy varied. Each patient was given a personalized approach to rehabilitation intervention, taking into account the degree of functional joint disability, participation in work life and psychosocial issues.